Pengaruh Gaya Hidup (Life Style), Harga (Price), dan Kelompok Referensi (Reference Group) terhadap Keputusan Pembelian Telepon Seluler Blackberry (Studi Pada Mahasiswa Program S1 Angkatan 2009 Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro) - Afrida Fatharani; Nawazirul Lubis; Reni Shinta Dewi (Universitas Diponegoro, 2013)
High of competition motivated costumer to selective measures in purchase decision. Consumers purchase decision affected by many factors, between life style, price, and reference group. Based on that, problem in this research is decline of Blackberry user amount at 2010 in over midst rise of user amount in every year during 6 latest years. This research purpose to find out whether have influences between life style, price, and reference group on purchase decisions.This research used explanatory research. From 239 research population taked 71 respondents as sample with Simple Random Sampling method. Collecting data used questionnaire. Analysis data used correlation coefficient, determination coefficient, regression analysis, t test, and F test.The Result this research show that life style, price, and reference group have positive influence and significant on purchase decisions in partial (with result as bis as 40,6%, 41,7%, and 50,8% for each variable) as well as in simultaneous as big as 70,6% with reference group gave biggest influence.For Research in Motion (RIM) proposed to create with catchy design and establish price fits specification and product quality cause many competitors offering telephone cellular product with more excellent specification along with attractive features with affordable price like telephone cellular with Android operating system. For next research need to research about factors be sides life style, price, and reference group influences on purchase decisions